School-based sexual health education interventions to prevent STI/HIV in sub-Saharan Africa: a systematic review and meta-analysis - A. Sadiq Sani; Charles Abraham; Sarah Denford; Susan Ball (BMC, 2016)
Abstract Background School-based sexual health education has the potential to provide an inclusive and comprehensive approach to promoting sexual health among young people. We reviewed evaluations of school-based sexual health education interventions in sub-Saharan Africa to assess effectiveness in reducing sexually transmitted infections and promoting condom use. Methods We searched ten electronic databases, hand-searched key journals, and reference lists of included articles for potential studies. Data were extracted on outcomes, intervention characteristics, methods and study characteristics indicative of methodological quality. Where possible, data were synthesized using random effect meta-analysis. Intervention features found predominantly in effective interventions were noted. Results The initial search retrieved 21634 potentially relevant citations. Of these, 51 papers reporting on 31 interventions were included. No evaluation reported statistically significant effects on the incidence or prevalence of Human Immunodeficiency Virus and Herpes Simplex Virus 2 infections. However, intervention participants reported statistically significant greater condom use in both randomised controlled trials and non-randomised trials for short (less than 6 months) follow-up periods (OR = 1.62, 95 % CI = 1.03-2.55 and OR = 2.88, 95 % CI = 1.41-5.90 respectively). For intermediate (6-10 months) and long-term (more than 10 months) follow-up periods, the effect was statistically significant (OR = 1.40, 95 % CI = 1.16-1.68) and marginally significant (OR = 1.22, 95 % CI = 0.99-1.50) among the randomised trials respectively. Only 12 of the 31 interventions reported implementation details, out of which seven reported on fidelity. Conclusion School-based sexual health education has the potential to promote condom use among young people in sub-Saharan Africa. However, further work is needed to develop and evaluate interventions that have measurable effects on sexually transmitted infections.